PELAKSANAAN PERJANJIAN PEMBIAYAAN DENGAN JAMINAN FISDUSIA ANTAR PT. ARJUNA FINANCE DENGAN DEBITUR DI KABUPATEN KAMPAR - Sarthi, Ully Trand; Bachtiar, Maryati; Fitriani, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
The public’s need for financing is now increasingly high, along with thedevelopment of technology, the necessities of life are also increasing following theflow of security developments, so that there are also many financing institutions,both bank and non- bank financing institutions , where the financing institution isthe goal of society to meet their needs, especially financing. Both financinginstitutions in the form of provision of funds and capital goods, one of which isPT. Arjuna Finance. The objectivesof this thesis are:first, to find out the rights and obligationsof the parties in the financing agreement with a fiduciaryguarantee between PT.Arjuna Finance and debtors in Kampar Regency; Second to find out the legalconsequences that arise in the event of default in the financing agreement with afiduciary guarantee between PT. Arjuna Finance with debtors in KamparRegency.where the debtor of PT.Arjuna Finance still has many violations of thelaw namely defaults without meeting an achievement that has been agreed uponor mutually agreed upon with the creditor.The type of legal research used by the author is a type of sociological legalresearch and can also be said to be field research,which is to study the applicablelegal provisions and what happens in the reality of society with the intention ofknowing and finding the required facts and data. While the nature of this researchis descriptive qualitative by providing a general explanation of theimplementation of the financing agreement with a fiduciary guarantee betweenPT. Arjuna Finance with debtosr in Kampar Regency.The results of this study are that in the implementation of the financingagreement with fiduciary guarantee between PT. Arjuna Finance and the debtorsin kampar regency, it does not fully run according to the agreement agreedbetween the debtors and the creditor. This is due to the existence of customerswho do not exercise their rights and obligations as good debitor so that there arestill many debitor who default in the financing agreement with the fiduciaryguarantee of PT. Arjuna Finance. Keywords: Agreement, Debtors, Creditors, Implementation, Fiduciary